Family Literacy and Revitalization of Islamic Values In Indonesia - Tubagus Chaeru Nugraha; Rosaria Mita Amalia; Fahmy Lukman; Davidescu Cristiana (Perhimpunan Intelektual Muslim Indonesia, 2021)
The industrial revolution 4.0 disrupts the technology field and other fields, such as law, economics, and society, namely the deprivation of human values and religion. One of the steps to overcome the disruption era is the revitalization of Islamic values, given that the majority of Indonesia's population is Muslim. Islamic values ​​are fundamentally built in the family as the smallest social structure of society. Therefore, this study aims to describe the strategy of the revitalization of Islamic values ​​in the family. To achieve this goal, a descriptive analysis method is used. To obtain accurate results, this study was conducted in three steps. First, the provision of data with the method of conversation with questionnaire techniques about Islamic values ​​in the family which one of the members is the student. Second, the analytical method used is the eclectic SWAT-functional method. Using SWAT-analysis as one of the methods, the strengths, weaknesses, threats, and challenges of the family to revitalize Islamic values ​​in the era of disruption can be mapped, while using the functional analysis, it can be given the principles of Islamic families. Then, the analyzed data is compiled as a strategy to revitalize Islamic values ​​in the family. Third, the presentation of data informally, namely providing a straightforward explanation of optimizing Strengths-opportunities and strategies to overcome weaknesses (weakness-threats) to revitalize Islamic values ​​in the family. The results of the study were found two types of Indonesian families based on the eight family functions in the Qur'an. Type-A, a good family and strong, namely the fulfillment of family functions between 70% to 90%. The type-B family is not good and not strong because religion and education are not good. This research implies that a strategy is needed to optimize the value of Islamic values in the type A family and strengthen the religiosity function and educational function in the type B family.